Short Communication: Ethnobotanical study of Lygodium circinnatum and its utilization in crafts weaving in Indonesia - Mulyati Rahayu; Emma Sri Kuncari; Mahdawia; Marwan Setiawan (Society for Indonesian Biodiversity, 2020)
Abstract. Rahayu M, Kuncari ES, Mahdawia, Setiawan M. 2020. Short Communication: Ethnobotanical study of Lygodium circinnatum and its utilization in crafts weaving in Indonesia. Biodiversitas 21: 617-621. Lygodium circinnatum (Burm.f.) Swartz, locally known as ketak, is a species of ferns that is currently widely used as raw material for making woven artifacts. In Indonesia, the center of L. circinnatum handicrafts, among others, is the island of Bali, Lombok and the city of Kendari. A variety of products are in great demand, not only by domestic tourists but also by foreign tourists. Cultivation of L. circinnatum has not been undertaken effectively, therefore raw material supply is still from wild populations. This ethnobotanical study conducted to review the traditional use of L. circinnatum and its cultivation efforts. This is essential as the use value of the L. circinnatum is increasing and also to ensure the continued availability of raw materials.